2018
DOI: 10.1016/j.beproc.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Systematic assessment of food item preference and reinforcer effectiveness: Enhancements in training laboratory-housed rhesus macaques

Abstract: The use of systematic preference assessments can enhance positive reinforcement training with captive animals. We found that the multiple stimulus without replacement (MSWO) technique identified food preferences in laboratory housed rhesus macaques, with raisins and grapes being ranked higher on average than dried apricot, pasta, and green beans (Friedman Test, χ2 (4) = 35.52, p < .001). Agreement between individuals (N = 21) was moderate (Kendall’s W = .42), and consistency across time varied among individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 54 publications
2
34
0
Order By: Relevance
“…Additionally, a forced-choice paradigm would possibly yield similar results; however, this method may not be as time-effective since the animals would require training on the task (Fisher et al, 1992). indicating that animals may habituate to preferred items over time, decreasing the effectiveness of once desired items (Clay, Bloomsmith, Marr, & Maple, 2009;Martin et al, 2018;Wells & Egli, 2004). In two studies testing preference assessment in primate species, it was found that both species' preferences were not consistent over a year's time (Clay et al, 2009;Martin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a forced-choice paradigm would possibly yield similar results; however, this method may not be as time-effective since the animals would require training on the task (Fisher et al, 1992). indicating that animals may habituate to preferred items over time, decreasing the effectiveness of once desired items (Clay, Bloomsmith, Marr, & Maple, 2009;Martin et al, 2018;Wells & Egli, 2004). In two studies testing preference assessment in primate species, it was found that both species' preferences were not consistent over a year's time (Clay et al, 2009;Martin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Zoo researchers may use novel forms of technology for assessment (Hopper, Egelkamp, Fidino, & Ross, 2019; Huskisson, Jacobson, Egelkamp, Ross, & Hopper, 2020) or use one of the numerous adaptations of this measure (Dorey, Mehrkam, & Tacey, 2015; Fay & Miller, 2015; Fernandez & Timberlake, 2019; Fernandez, Dorey, & Rosales‐Ruiz, 2004; Gaalema et al, 2011; Mehrkam & Dorey, 2014, 2015; Roane, Vollmer, Ringdahl, & Marcus, 1998). In the past, researchers have conducted food preference assessment to discover favored items to be used as reinforcers for positive reinforcement training (Fernandez et al, 2004; Gaalema et al, 2011; Martin, Franklin, Perlman, & Bloomsmith, 2018). Gaalema et al (2011) took an additional step by testing the effectiveness of the preferred items as reinforcers through the amount of control the item had on a behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we controlled the distribution of dates and peanuts and other palatable treats to our monkeys. Other labs have also now reported similar practices (Martin et al, 2018). We believed these food items are a key motivator for the monkeys during their training sessions, so we used them as rewards during training only.…”
Section: Methodsmentioning
confidence: 79%
“…Out of these studies, only one study reported the implementation of some form of reinforcer preference assessment, though it was not systematic in nature (i.e., a variety of food rewards was presented to the owners and/or the dogs to choose from). This lack of preference assessment in the identified literature is an unexpected finding, since a growing body of literature has already highlighted the value of conducting preference assessments in animal behavior interventions across the settings, species, and stimuli examined (e.g., food or toys [ 79 , 97 , 98 , 99 , 100 ]). Overall, research shows that the delivery of a pre-established preferred stimulus as a reinforcer may improve the intervention outcome relative to the use of arbitrarily selected items with a presumed reinforcing function (e.g., assumed by the animals’ caregivers [ 79 , 99 , 101 ]).…”
Section: Discussionmentioning
confidence: 99%